THE DESIGN AND TESTING OF ADSORPTION REFRIGERATION SYSTEM WITH TWO ADSORBERS - Andi Taufan; Nasruddin Nasruddin (Widyariset, 2013)
This paper discusses design and testing of adsorption refrigeration system with two adsorbers. Main components consisted of two adsorber with 6.6 kg solidified activated carbon inside, expansion valve, evaporator, condenser, and reservoir. All of that were connected with stainless steel pipes. The test performed for 75 minutes using 250 ml of methanol pro-analysis of 99.9% as a refrigerant in the system and the water temperature is 250C which is pumped through copper pipes to cool the adsorbents. The air pressure in the system during the test were in vacuum. The average pressure difference between the adsorber and the evaporator during testing was 4.6 cmHg. The lowest temperature was 140C obtained after the 65th minute.